2018
DOI: 10.1136/bcr-2018-226292
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic pyloric stenosis following repair of oesophageal atresia and tracheo-oesophageal fistula in a neonate

Abstract: Development of hypertrophic pyloric stenosis (HPS) after a few weeks of repair of an oesophageal atresia (OA) and tracheo-oesophageal fistula (TOF) is a rare condition in early infancy. Although vomiting or feeding intolerance in operated cases of OA+TOF are attributed to oesophageal stricture, gastro-oesophageal reflux and oesophageal dysmotility, it may also be caused by HPS. Herein, we report a newborn infant who had OA and TOF operation on day 2 of life and diagnosed to have HPS at 15th day of age. Even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Last, IHPS could also be the result of the atresia itself, potentially as a result of the surgical procedure or the postoperative treatment. Previous studies have suggested vagal nerve lesions, a gastrostomy and transpyloric feeding tubes as possible causes for an increased incidence of IHPS after correction of EA (Ilhan, Bor, Gunendi, & Dorterler, 2018). IHPS has been suggested to be a neuromuscular disorder with the involvement of smooth muscle cells, interstitial cells of Cajal and the enteric nervous system.…”
Section: Ihps Might Be An Acquired Condition Related To Surgery or mentioning
confidence: 99%
“…Last, IHPS could also be the result of the atresia itself, potentially as a result of the surgical procedure or the postoperative treatment. Previous studies have suggested vagal nerve lesions, a gastrostomy and transpyloric feeding tubes as possible causes for an increased incidence of IHPS after correction of EA (Ilhan, Bor, Gunendi, & Dorterler, 2018). IHPS has been suggested to be a neuromuscular disorder with the involvement of smooth muscle cells, interstitial cells of Cajal and the enteric nervous system.…”
Section: Ihps Might Be An Acquired Condition Related To Surgery or mentioning
confidence: 99%